The Position of the Constitutional Court in Strengthening the Democratic System - Gusthomi, Moh Imam; Daud Renata Candra Ramadan,; Anis Widyawati,; Zulfa Rena Wijayanti,; Adiba Ro’uf Danur Islam, (Semarang State University Undergraduate Law and Society Review, 2025)
The Constitutional Court is one of the institutions that had an important role in strengthening the democracy. This institution is not only tasked with testing the law on the 1945 Constitution of the Republic of Indonesia, but also as a guardian of democratic values and constitutionality in various state policies. This study aims to explore more deeply how the Constitutional Court lives its functions in building a healthy, stable, and fair democratic system. In many cases, the Constitutional Court has become the last place for citizens in fighting for their rights that are considered neglected by existing regulations. Some important decisions that have been issued show their alignments on the protection of human rights and social justice, which is a pillar of democracy itself. The Constitutional Court also performed the function as a counterweight in the Trias Politica system, especially in setting the potential for abuse of power from the executive institution and legislative. In this case, the Court is not only reactive to the application, but also shows a proactive attitude in maintaining constitutional values so as not to be violated by the authorities. The methods used in this study are normative research with statutory and conceptual approaches and literature studies. The existence of the Constitutional Court is not just a symbol of law, but also an essential control tool in creating political balance, ensuring people's participation, and maintaining democracy in the midst of challenges that are changing. The Constitutional Court plays a central role in strengthening the constitutional democratic system in Indonesia. In this system, which emphasizes the supremacy of the constitution, the protection of human rights, the separation of power and the organization of democratic elections, the Constitutional Court acts as the guardian of the constitution and balancing of state power.